PERAN MANAJEMEN BERBASIS SEKOLAH DALAM RANGKA PENINGKATAN PROFESIOLISME GURU PENJASKES - Basuki, Sunarno (Multilateral Jurnal Penjas Or, 2012)
Abstrak: School Based Management (SBM) is a standard in the management of educational units as mandated by Act No.20 of 2003 on National Education System Article 51 (1). It provides a foundation for schools to independently manage and develop the school. The professionalism of teachers as an important part in improving the quality of education in schools can be backed up by the School-Based Management system. The implementation of the SBM is not only on the level of the school or organization, but also up to the level of teachers and students. Teachers of physical education and sport can apply the principles of school-based management to enhance their professionalism. Some things which can be implemented namely: identification of real problems, arranging plan and program quality, identifying the functions required to achieve goals, SWOT analysis, implementation of program and evaluation. The management Pattern will lead the teachers to be more professional. Key Words: MSB, Professionalism, Physical and health education teacher Abstrak: Manajemen Berbasis Sekolah (MBS) merupakan standar dalam pengelolaan satuan pendidikan seperti yang diamanatkan oleh UU No.20 tahun 2003 tentang Sistem Pendidikan Nasional Pasal 51 (1). Hal tersebut memberikan dasar bagi sekolah untuk mandiri dalam mengelola dan mengembangkan sekolah. Profesionalisme guru sebagai bagian penting dalam meningkatkan mutu pendidikan di sekolah dapat didukung dengan adanya sistem pengelolaan Manajemen Berbasis Sekolah. Impelementasi MBS tidak hanya sampai pada tingkat sekolah atau organisasi, tetapi juga sampai tingkat  guru dan siswa. Guru pendidikan jasmani dan olah raga dapat menerapkan prinsip-prinsip dari manajemen berbasis sekolah guna meningkatkan profesionalismenya.  Beberapa hal dapat diimplementasikan, yaitu : identifikasi masalah yang nyata, menyusun rencana program dan mutu, identifikasi fungsi-fungsi yang diperlukan mencapai sasaran, analisis SWOT, pelaksanaan program dan evaluasi. Pola manajemen seperti itu akan mengarahkan guru penjaskes lebih profesional. Kata Kunci : MSB, Profesionalisme, guru penjaskes